Pollution threatens water quality in the Central Marshes of Southern Iraq (Baghdad Science Journal, 2021)
Water pollution is an issue that can be exacerbated by drought as increased concentrations of unwanted substances are a consequence of lower water levels. Polluted water that flows into natural marshlands leads to the deposition of pollutants in the interior of the marsh. Here we present evidence that the interior of the Central Marsh (CM) in southern Iraq suffers from higher levels of pollution than areas closer to the source of water entering the marsh (the Euphrates River). A 1.7m embankment that halts the flow of the Euphrates is only infrequently breached and so the CM is effectively the terminal destination of the waters (and their associated pollutants and agricultural waste) flowing from the West of Iraq.A range of water quality metrics were measured where the Euphrates enters the CM and at increasing distances into the interior of the CM. The following measures were taken:  NO2, NO3, PO4 , Salinity, Major ions, and Heavy Metals (Cu, Ni, Pb, Cd, Zn). The area of study was divided into four horizontal zones (the river and three zones inside the marsh) and eight field surveys were carried out from November 2013 to June 2014 to collect water samples by using a transect line methodology. Salinity and major ions (Na, K, Cl, Ca, and Mg) were significantly higher inside the marsh compared with levels in the river water immediately before it entered the CM.  These findings indicate  the increased risk of these pollutants to humans and wildlife living in and using the CM.  This issue  requires urgent attention, especially to the status of the CM as a World Heritage site (for the ecosystem services provided to local people) as an Important Biodiversity Area. The reported declines in water quantity in the Euphrates over recent decades will likely further exacerbate the problems we report.Supplement file